2015
DOI: 10.19173/irrodl.v16i2.2019
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines towards the facilitation of interactive online learning programmes in higher education

Abstract: The creation of online platforms that establish new learning environments has led to the proliferation of institutions offering online learning programmes. However, the use of technologies for teaching and learning requires sound content specialization, as well as grounding in pedagogy. While gains made by constructivism and observational learning are well documented, research addressing online practices that best encourage constructivist and observational learning in Open and Distance Learning (ODL) contexts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 22 publications
1
24
0
8
Order By: Relevance
“…As first year undergraduates, it is good to note that (42.3 and 35.2) were not intimidated but developed more confidence (57.7 and 15.5) in the use of OER. This supported Rogers (2003) and Mbati and Minnar (2015) that believed that trialability is positively related to the likelihood of adoption. Table 5 indicates that majority of undergraduates (46.5 and 35.2) have not seen the use of OER before or heard from other schools.…”
Section: Resultssupporting
confidence: 76%
“…As first year undergraduates, it is good to note that (42.3 and 35.2) were not intimidated but developed more confidence (57.7 and 15.5) in the use of OER. This supported Rogers (2003) and Mbati and Minnar (2015) that believed that trialability is positively related to the likelihood of adoption. Table 5 indicates that majority of undergraduates (46.5 and 35.2) have not seen the use of OER before or heard from other schools.…”
Section: Resultssupporting
confidence: 76%
“…Additionally, further research should focus on examining how such blends and trainings can best be made and how aspects like an appropriate facilitator-student ratio may be most effectively planned and maintained. Mbati and Minnaar (2015) identify this issue as one of the biggest concerns in online education, given that there are frequently large numbers of students per facilitator, though this problem seems very frequently ignored by educational stakeholders. If current learners (often referred to as millennials or digital natives) are to be offered efficient online learning environment opportunities, regardless of their economic, social, linguistic, or disability backgrounds, educational systems must strive to meet their needs and preferences.…”
Section: Discussionmentioning
confidence: 99%
“…While this initiative is commendable, the extent to which UNISA lecturers explore various e-learning technologies, tools, and applications, as well as implement innovative approaches to support students' learning is unclear and has not been fully researched. A 2015 study (Mbati & Minnaar, 2015) of online learning indicated that online facilitators were not using social media technologies to support and enhance students' learning. A more recent study (Ngubane-Mokiwa, 2017) indicated that some UNISA lecturers are reluctant to use modern technologies because "modern electronic technologies force traditionally-inclined lecturers out of the comfort zone of their customary familiar techniques and pedagogies" (p. 118).…”
Section: Introductionmentioning
confidence: 99%